2001
DOI: 10.4049/jimmunol.167.4.2187
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Lysocardiolipin Is Exported from Phagosomes upon Cleavage of Cardiolipin by a Macrophage-Derived Lysosomal Phospholipase A2

Abstract: Pathogenic mycobacteria are able to survive and proliferate in phagosomes within host macrophages (Mφ). This capability has been attributed in part to their cell wall, which consists of various unique lipids. Some of these are important in the host-pathogen interaction, such as resistance against microbicidal effector mechanisms and modulation of host cell functions, and/or are presented as Ags to T cells. Here we show that two lipids are released from the mycobacterial cell wall within the phagosome of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 33 publications
2
61
0
Order By: Relevance
“…Lysobisphosphatidic acid and phosphoinositides regulate release of VSV nucleocapsid into cytoplasm [13] SigD/SopB is a type III bacterial derived phosphoinositide phosphatase [29,112] Molecular species of phosphatidylcholine and phosphatidylethanolamine are altered in host plasmamembrane after Plasmodium infection [116] GP Ethanolamine phospholipids required for Sindbis virus production [111] Intracellular mycobacteria release a heterogeneous mixture of lipids [27,113] Growth arrest of Plasmodium [117] and Toxoplasma [85] by disruption of phosphatidylcholine synthesis Semliki Forest virus mRNA capping enzyme requires association with anionic membrane phospholipids for activity [14] Phosphatidylinositol mannosides stimulate fusion of early endosomes with mycobacterial phagosomes [30] Glycosylated phosphatidylinositol causes phagosome maturation arrest [114] SapM, a mycobacterial derived phosphatase hydrolyses PI3P contributing to inhibition of phagolysosome maturation [115] Sphingosine 1-kinase is recruited to nascent phagosomes [118] Inhibition of sphingolipid biosynthesis in T. gondii blocks replication [119] SP Sphingomyelin metabolism important for P. falciparum development [120] Inhibition of cholesterol biosynthesis inhibits Hepatitis C virus RNA replication [15] Inhibition of cholesterol acquisition by the host lowers T. gondii replication [40] ST Cholesterol esterification essential for optimal T. gondii proliferation [121,122] Isopreonoid synthesis inhibitors with anti-malarial [123] and anti-T. gondii activity [124] PR Block of protein farnesylation as antiapicomplexan therapies [125] 5…”
Section: Glmentioning
confidence: 99%
“…Lysobisphosphatidic acid and phosphoinositides regulate release of VSV nucleocapsid into cytoplasm [13] SigD/SopB is a type III bacterial derived phosphoinositide phosphatase [29,112] Molecular species of phosphatidylcholine and phosphatidylethanolamine are altered in host plasmamembrane after Plasmodium infection [116] GP Ethanolamine phospholipids required for Sindbis virus production [111] Intracellular mycobacteria release a heterogeneous mixture of lipids [27,113] Growth arrest of Plasmodium [117] and Toxoplasma [85] by disruption of phosphatidylcholine synthesis Semliki Forest virus mRNA capping enzyme requires association with anionic membrane phospholipids for activity [14] Phosphatidylinositol mannosides stimulate fusion of early endosomes with mycobacterial phagosomes [30] Glycosylated phosphatidylinositol causes phagosome maturation arrest [114] SapM, a mycobacterial derived phosphatase hydrolyses PI3P contributing to inhibition of phagolysosome maturation [115] Sphingosine 1-kinase is recruited to nascent phagosomes [118] Inhibition of sphingolipid biosynthesis in T. gondii blocks replication [119] SP Sphingomyelin metabolism important for P. falciparum development [120] Inhibition of cholesterol biosynthesis inhibits Hepatitis C virus RNA replication [15] Inhibition of cholesterol acquisition by the host lowers T. gondii replication [40] ST Cholesterol esterification essential for optimal T. gondii proliferation [121,122] Isopreonoid synthesis inhibitors with anti-malarial [123] and anti-T. gondii activity [124] PR Block of protein farnesylation as antiapicomplexan therapies [125] 5…”
Section: Glmentioning
confidence: 99%
“…Processing and presentation of a microbial phospholipid resembling a host lipid are understandable in this light. Although mycobacterial CL has not previously been shown to be presented by CD1 or recognized by T lymphocytes, it can be cleaved by lysosomal enzymes present in mammalian macrophages (Fischer et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…TDM toxicity is due to an increase of the tissue specific nicotinamide adenine dinuclease activity decreasing the levels of NAD in several tissues by blocking the electron flow along the (Artman et al, 1964;Barry et al, 1998;Brennan, 2003). During infection and when inside of the phagosome, M.tb is shown to produce large quantities of TDM (Fischer et al, 2001). From many studies d o n e o n T D M , i t i s r e m a r k a b l e t h a t TDM induces lung granulomas and has immunostimulating properties (Bekierkunst, 1968) that are probably at the origin of its antitumoral activity (Bekierkunst et al, 1971a) (Table 1).…”
Section: The Peripheral Lipid Layer In the M Tuberculosis Cell Wallmentioning
confidence: 99%
“…These are phosphatidylglycerol, diphosphatidylglycerol (DPG) and phosphatidylethanolamine. Although the role of these M.tb cell wall phospholipids during infection is uncertain, M.tb cardiolipin (a DPG molecule) is shown to be processed into lysocardiolipin by the lysosomal phospholipase A 2 during M.tb infection (Fischer et al, 2001). Antibodies against M.tb cardiolipin are also found in sera from TB patients (Santiago et al, 1989), and their production is shown to be strictly related to IL-4 and T cells (Fischer et al, 2002).…”
Section: The Peripheral Lipid Layer In the M Tuberculosis Cell Wallmentioning
confidence: 99%
See 1 more Smart Citation